Pengaruh Gaya Kepemimpinan dan Pemberian Bonus Terhadap Loyalitas Karyawan PT. Astra Sedaya Finance - Purba, Riswan; Waruwu, Khamo; Yunita, Mella; Amirudin, Amirudin (CV. ITTC INDONESIA, 2021)
In a research work has a purpose, where the research was conducted to determine the influence of leadership style and giving bonuses to employee loyalty at PT. Astra Sedaya Finance Medan Branch. This research was conducted at PT. Astra Sedaya Finance Medan Branch, with a population and sample of 85 employees, including contract employees. The research instrument is a questionnaire/questionnaire with a Likert scale model. The requirements test is carried out by testing the validity and reliability tests as well as the classical assumption test. The data analysis technique used is multiple regression technique at a significance level of = 0.05. In testing the first hypothesis, it has partially proven that there is an influence between Leadership Style on Employee Loyalty with a significant value level of 0.000 <0.05, thus Ha is accepted and Ho is rejected. Then partially testing the second hypothesis has proven that the effect of Bonus Giving on Employee Loyalty has a significant effect of 0.000 < 0.05. Thus Ha is accepted, H0 is rejected. Furthermore, the F test proves that two independent variables have a simultaneous influence on the dependent variable with a significant value of F count 0.000 <0.05 which is declared to have a positive and significant effect. From the results of the coefficient of determination of the value of R Square, all independent variables have an influence with a percentage of 41.1% and the excess is influenced by other factors, which are 58.9% which is not yet known.